PENGARUH PEMBERIAN BENTUK UMPAN BALIK (FEEDBACK) TERHADAP HASIL BELAJAR MATEMATIS SISWA KELAS VII SMP - Irma Helenia; Zubaidah Zubaidah; Bistari Bistari (Universitas Tanjungpura, 2017)
AbsractThis research aims to find out the effect of granting feedback in students’ learning outcomes at seventh grade of SMPN 04 Singkawang in the set topic. This research used experimental method with experimental research design. The sampel of this research was 32 student of class VII A, 32 student of class VII B, 32 student of class VII E as experiment class. This research showed that the average of the learning outcomes mathematical of students with provision of feedback form. The data analysis result showed that there is no difference feedback form but viewed from the large effect size gives the value of different effect size and highest is the form of explanatory feedback with the effect size value of 0,1327. Keyword: Granting feedback, Learning Outcomes